Big broad banks: How does cross-selling affect lending? - Yingjie Qi (Sveriges Riksbank, 2020)
Using unique micro-data that contain the internal information on all corporate customers of a large Nordic bank, I show that combining loan and non-loan products (cross-selling) has two benefits. First, it increases credit supply, especially in recessions. Second, it increases the likelihood of receiving lenient treatment in delinquency. I argue that non-loan relationships play an important role in determining credit supply and debt renegotiation, not only by (i) mitigating information asymmetries (as suggested in earlier literature), but also by (ii) increasing the profitability of the relationship. Exploiting an exogenous and differential change in similar products' profitability due to the Basel II implementation, I estimate the causal effect of this new profit channel on credit supply. A 20 percent decrease in non-loan products' profitability (i) reduces credit supply to affected firms by 13 percent (600,000 USD) compared with unaffected firms, and (2) reduces likelihood of receiving lenient treatment for affected firms by 30 percent (13 pp) compared with unaffected firms, conditional on being delinquent.
Keywords: G01; G21; G28; 330; relationship banking; cross-selling; credit allocation; debt renegotiation; financial distress